Pengaruh Konservatisme Akuntansi, Alokasi Pajak Antar Periode, dan Investment Opportunity Set terhadap Kualitas Laba - Ayem, Sri; Lori, Elisabeth Elen (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aimed to determine: (1) the background of the purpose of this study is to determine the influence of conservatism accounting, inter-period tax allocations, and investment opportunity set on earning quality. The study used a sample of manufacturing companies listed on Indonesian Stock Exchange (IDX) during the 2016-2018 period. The number of samples used in this study were 18 companies with 3-year observations using purposive sampling method. Data processing using SPSS version 22 with multiple linear regression. The results showed that conservatism accounting and investment opportunity set had a positive effect on earning quality, while inter-period tax allocations is not effect on eaning quality.